Morphology of breeze circulations induced by surface flux heterogeneities and their impact on convection initiation. (19th December 2016) - Rochetin, Nicolas; Couvreux, Fleur; Guichard, Françoise
Abstract : This study analyses the role of breeze circulations induced by a surface sensible heat flux heterogeneity on deep convection initiation. Large‐eddy simulations are used to disentangle the processes at play in a typical case of daytime triggering of deep convection over a semi‐arid land. We show that the presence of a realistic surface sensible heat flux heterogeneity leads to an earlier triggering of convection and induces a strong determinism in the triggering location at the beta‐mesoscale (i.e. ∼50 km). The transition to deep convection consists of three consecutive stages, each one corresponding to a specific mode of interaction between (i) the boundary‐layer thermals (small‐scale), (ii) the breeze circulation (mesoscale) and (iii) the background wind (synoptic scale). These stages are both interpreted thermodynamically and morphologically. All along the transition phase, the boundary‐layer growth acts to slow down the background wind, which strengthens the breeze circulation. The breeze evolves towards a circular shape which optimizes moisture convergence and cloud formation just prior to triggering. The presence of wind shear leads with a more asymmetric shape of the breeze in the afternoon, associated with a preferential triggering on the down‐shear side of the breeze circulation.